Peri-implantitis at implants with different diameters: a pilot study in dogs - Fabrizio Morelli; Karol Alí Apaza Alccayhuaman; Paolo Viganò; Franco Bengazi; Joaquin Urbizo; Gianfranco Cesaretti; Daniele Botticelli (SpringerOpen, 2019)
Abstract Aim To evaluate the progression of an induced peri-implantitis at implants with different diameters and the outcome of a corrective surgical debridement. Methods Three months after the extraction of the mandibular premolars and first molars in six dogs, non-submerged narrow implants (3.3 mm in diameter) or standard implants (3.8 mm and 4.1 mm) were installed in the molar regions, bilaterally. After 3 months, peri-implantitis lesions were induced with ligatures and plaque accumulation for 3 months. Plaque accumulation was allowed for a further month after ligatures removal. A surgical mechanical decontamination of the surfaces was subsequently performed using gauzes soaked in saline and irrigation. Five months after, biopsies were retrieved and histological slides prepared. X-rays were taken at treatment and 5 months after. Results Fourth months after peri-implantitis induction, 2.2 ± 1.0 mm at the standard implants and 3.2 ± 0.4 mm at the narrow implants were observed. Five months after treatment, a mean gain of marginal bone of 0.5 ± 0.6 mm was obtained at the standard implants and of 0.9 ± 0.4 at the narrow implants (p = 0.249). The vertical and horizontal defects were found partially closed. At the histological analysis, the coronal level of osseointegration after 5 months of healing was at 2.1 ± 0.8 mm at the standard implants, and 2.8 ± 0.3 mm at narrow implants (p = 0.116). Conclusions In conclusion, the narrow implants showed a tendency of a faster progression of the induced peri-implantitis compared to standard implants. The implant diameter did not influence the outcome of a surgical treatment of an induced peri-implantitis.